Racial Disparities in Epigenetic Aging of the Right vs Left Colon. (30th December 2020) - Devall, Matthew; Sun, Xiangqing; Yuan, Fangcheng; Cooper, Gregory S; Willis, Joseph; Weisenberger, Daniel J; Casey, Graham; Li, Li
Abstract: There are well-documented racial differences in age-of-onset and laterality of colorectal cancer. Epigenetic age acceleration is postulated to be an underlying factor. However, comparative studies of side-specific colonic tissue epigenetic aging are lacking. Here, we performed DNA methylation analysis of matched right and left biopsies of normal colon from 128 individuals. Among African Americans (n = 88), the right colon showed accelerated epigenetic aging as compared with individual-matched left colon (1.51 years; 95% confidence interval [CI] = 0.62 to 2.40 years; 2-sided P  =   .001). In contrast, among European Americans (n = 40), the right colon shows remarkable age deceleration (1.93 years; 95% CI = 0.65 to 3.21 years; 2-sided P  =   .004). Further, epigenome-wide analysis of DNA methylation identifies a unique pattern of hypermethylation in African American right colon. Our study is the first to report such race and side-specific differences in epigenetic aging of normal colon, providing novel insight into the observed younger age-of-onset and relative preponderance of right-side colon neoplasia in African Americans.